ANALISIS STRATEGI MANAJEMEN SUMBER DAYA MANUSIA (MSDM) DALAM MENIGKATKAN MUTU PELAYANAN DI RSUD ARIFIN ACHMAD POVINSI RIAU - Nadiah Salsabila; Muhammad Firdaus, Bobi Handoko, Anatasya Shinta Yuliana (CV. Adiba Aisha Amira, 2024)
Hospital human resource management (HRM) is a system that requires special attention in order to be as effective and efficient as possible in managing human resources so that they can compete with other hospitals, both private and government. Quality human resources have an effect on improving the service quality of a hospital, one of which is RSUD Arifin Achmad Riau Province. This study aims to determine the strategy of human resource management (HRM) in improving service quality at Arifin Achmad Hospital, Riau Province. This type of research is qualitative with an analytic descriptive approach. This research was conducted on 9 February - 30 June 2023 at Arifin Achmad Hospital, Riau Province. There are 4 informants in this study and this research uses the Content Analysis model. The results showed that there were patient satisfaction surveys through print and electronic media, unscheduled and evenly distributed employee training, distribution of rewards that were not scheduled regularly, provision of replacements for old damaged goods, there were still units that had not displayed SOPs, no employee reserves, errors. data entry and room delivery, use of modern applications for attendance. It can be said that the Human Resource Management at Arifin Achmad Hospital in Riau Province is not fully optimal. It is suggested that there should be training that is carried out consistently and evenly, setting a fixed period for giving rewards, displaying SOPs in all units, forming a special standby team and carrying out routine evaluations.